Effect of Ca doping on the arbitrary canting of magnetic exchange interactions in La1-xCaxMnO3 nanoparticles - Ali, Akhtar; Shah, Wiqar H.; Safeen, Akif; Ali, Liaqat; Tufail, Muhammad; Ullah, Zakir; Safeen, Kashif; Eldin, Sayed M.; R. Ali, Mohamed; Sohail, Muhammad; Imran, Naveed (Frontiers in Materials, 2023)
La1-xCaxMnO3 nanoparticles (x = 0.1, 0.2, 0.3) (LCMO NPs) were synthesized using the coprecipitation method. The prepared samples were investigated using x-ray diffraction (XRD), which confirmed the single-phase structure. The nanoparticle’s crystallite size was determined using Debye–Scherrer’s formula. Scanning electron microscopy showed that the size of the nanoparticles was between 33 nm and 55 nm. Energy-dispersive x-ray spectroscopy (EDX) was used to determine the elemental composition of samples. The four-probe method was used to measure the temperature-dependent electrical resistivity. Magnetic properties, such as hysteresis loop, magnetoresistance, and magnetization versus temperature, were measured using a vibrating sample magnetometer. The study of magnetization versus applied magnetic field M(H) showed that, at 77 K, all the loops exhibit ferromagnetism. DC magnetization versus temperature at a 70-Oe-applied field for all samples showed a paramagnetic-ferromagnetic phase transition. A decrease in Curie temperature Tc after increasing the concentration of x was observed. The real and imaginary parts of temperature-dependent ac magnetic susceptibility were measured and revealed a transition from the ferromagnetic to the paramagnetic phase at a particular temperature Tc, with DC magnetization behavior.